2012
DOI: 10.4103/0976-237x.94551
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic rehabilitation of a young patient with Hypophosphatasia - A review and case report

Abstract: Hypophosphatasia is a congenital disease characterized by deficiency of serum and tissue non-specific alkaline phosphatase activity. The disease occurs due to mutations in the liver/bone/kidney alkaline phosphatase gene. Six clinical forms of hypophosphatasia are recognized. Systemic symptoms of the disease are respiratory complications, premature craniosynostosis, widespread demineralization and rachitic changes in the metaphases, stress fractures, chondrocalcinosis and osteoarthropathy. Characteristic dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Some authors reported that a tendency towards a class III skeletal pattern increases with the severity of the hypodontia. [1] Balancing the occlusion relationship while enhancing the patient's facial aesthetics presented a significant challenge, [2] particularly when there was a reduction in upper lip protrusion. [3] The treatment approach for such cases differs for each individual.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported that a tendency towards a class III skeletal pattern increases with the severity of the hypodontia. [1] Balancing the occlusion relationship while enhancing the patient's facial aesthetics presented a significant challenge, [2] particularly when there was a reduction in upper lip protrusion. [3] The treatment approach for such cases differs for each individual.…”
Section: Introductionmentioning
confidence: 99%